Mathematical semantics: a dual history? 1965-1975 - Loh, Yi Fong (Nanyang Technological University, 2022)
The consolidation of knowledge formations into academic disciplines is a gradual process, whose transition is marked by institutional entrenchment and a gain in external legitimacy. While there’s a consensus in the historical literature that computer science had emerged as a new academic discipline by the late 1960s in America, it remains unclear when computing research became a scientific discipline in the UK. This thesis focuses on a particular a research programme in formal semantics, known as mathematical semantics that emerged from collaboration in 1969, beginning with its institutional origins in the Oxford Programming Research Group from 1965. Mathematical semantics, also known as Scott-Strachey semantics, is argued to be a site of disciplinary consolidation of computing research in the UK into computing science by the early 1970s. This account draws on primarily on scientific publications, archival material, and heretofore disparate disciplinary histories to flesh out an intertwined history of science that conjoins the histories of computing and mathematics in understanding disciplinary consolidation. This is informed by a mathematical literature review of what is now called domain theory. In concluding, I discuss how my historical account and its historiography sheds light on the history of computer science, especially with regard to the history of formal methods that mathematical semantics is a part of how historians can bring technical and sociohistorical perspectives into closer conversation with each other.